Advances in medium and high temperature solid oxide fuel cell technology - Boaro, Marta; Aricò, A. S. (Springer, 2017)
In this book well-known experts highlight cutting-edge research priorities and discuss the state of the art in the field of solid oxide fuel cells giving an update on specific subjects such as protonic conductors, interconnects, electrocatalytic and catalytic processes and modelling approaches. Fundamentals and advances in this field are illustrated to help young researchers address issues in the characterization of materials and in the analysis of processes, not often tackled in scholarly books.
Keywords: Solid oxide fuel cells.; elektronické knihy; electronic books